Concepts and Factors Influencing Independent Learning in IS Higher Education - Balapumi, Rohini; Aitken, Ashley (Deakin University, 2012)
The concepts of independent learning (IL), self-directed learning (SDL) and self-regulated learning (SRL) have been widely used in relation to students’ learning success. Often, these terms are interrelated and used interchangeably in the literature with regards to students’ learning process. The purpose of this paper is (1) to promote conceptual clarity by having clear definitions of SRL, SDL and IL and (2) to provide a review of research related to the development of students’ SRL at higher education particularly in the context of Information Systems studies. The findings from the literature reveal that mastering the process self-regulation progressively leads to self-directed and independent learning. The literature review on SRL reveals that students’ academic self-regulation is influenced by their personal processes such as cognitive knowledge and motivational beliefs and also external processes such as lecturers and instructions in higher education.